1997
DOI: 10.1164/ajrccm.155.4.9105096
|View full text |Cite
|
Sign up to set email alerts
|

Circulating IL-1ra and IL-10 levels are increased but do not predict the development of acute respiratory distress syndrome in at-risk patients.

Abstract: Although numerous cytokines, including interleukin (IL)-1, IL-8, and tumor necrosis factor, circulate in critically ill patients at risk for acute respiratory distress syndrome (ARDS), none clearly predict the development of the syndrome. We hypothesized that cytokines, such as IL-1ra, IL-10, and IL-4, which modulate inflammation, might contribute to or reflect the development of acute lung injury. Accordingly, serial levels of IL-1ra and IL-10 were measured in 77 patients who were identifed as being at risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 0 publications
5
32
1
Order By: Relevance
“…In contrast, initially high circulating levels of the proinflammatory cytokines IL-6 and monocyte chemotactic protein 1 (MCP1) and the main antiinflammatory cytokine IL-10 decreased over time. Serum levels of IL-5 and IL-8 were higher in nonsurvivors than in survivors, whereas both too-low and too-high levels of IL-6 as well as IL-10 were associated with a higher risk of organ failure and death (37)(38)(39). This U-shaped relationship is in agreement with the deleterious consequences of both the overwhelming proinflammatory response and the prolonged periods of immune suppression present in critical illness (reviewed in ref.…”
Section: Figuresupporting
confidence: 56%
“…In contrast, initially high circulating levels of the proinflammatory cytokines IL-6 and monocyte chemotactic protein 1 (MCP1) and the main antiinflammatory cytokine IL-10 decreased over time. Serum levels of IL-5 and IL-8 were higher in nonsurvivors than in survivors, whereas both too-low and too-high levels of IL-6 as well as IL-10 were associated with a higher risk of organ failure and death (37)(38)(39). This U-shaped relationship is in agreement with the deleterious consequences of both the overwhelming proinflammatory response and the prolonged periods of immune suppression present in critical illness (reviewed in ref.…”
Section: Figuresupporting
confidence: 56%
“…For instance, Aisiku et al reported that plasma IL-10, IL-6 and IL-8 were associated with development of ARDS in patients with severe traumatic brain injury [35]. Contradictorily, Parsons et al reported that circulating IL-1ra and IL-10 levels were increased but not related to the development of ARDS in at-risk patients [36]. In contrast to the high level of peripheral IL-10, the secretory IL-10 from BALF-derived macrophages was significantly repressed due to up-regulation of miR-211-5p, therefore the resolution of the local inflammation was seriously delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of IL-10 were found in patients with ARDS compared with critically ill non-ARDS patients [15]. Among ARDS patients, high plasma IL-10 but low bronchoalveolar lavage concentration of IL-10 correlated with increased mortality [16,17].…”
mentioning
confidence: 89%